2015
DOI: 10.1123/ijspp.2014-0484
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Physical and Technical Variability in the English Premier League

Abstract: Purpose:To investigate match-to-match variability of physical and technical performances in English Premier League players and quantify the influence of positional and contextual factors.Methods:Match data (N = 451) were collected using a multicamera computerized tracking system across multiple seasons (2005–06 to 2012–13). The coefficient of variation (CV) was calculated from match to match for physical and technical performances in selected positions across different match contexts (location, standard, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 25 publications
6
79
1
1
Order By: Relevance
“…Although these are the most intense sessions within the microcycle, whereby players are expected to produce repeated intense efforts, variation was still present, as the coaches constantly adjusted sessions because of the players' schedule, physical recovery status, and conditioning requirements for that week. Moreover, HSR and SPR distances are the metrics illustrating the most variability within the microcycle (.80%), which is consistent with the variability found in SSG formats (60-140%) (2) but lower than competition variability (20-30%) (14,16). The large variability in load across sessions and metrics seems to be a combination of the inherent unpredictable nature of game-based training and the strategies used by coaches to vary the stimulus for players to create training adaptations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although these are the most intense sessions within the microcycle, whereby players are expected to produce repeated intense efforts, variation was still present, as the coaches constantly adjusted sessions because of the players' schedule, physical recovery status, and conditioning requirements for that week. Moreover, HSR and SPR distances are the metrics illustrating the most variability within the microcycle (.80%), which is consistent with the variability found in SSG formats (60-140%) (2) but lower than competition variability (20-30%) (14,16). The large variability in load across sessions and metrics seems to be a combination of the inherent unpredictable nature of game-based training and the strategies used by coaches to vary the stimulus for players to create training adaptations.…”
Section: Discussionsupporting
confidence: 82%
“…Although elements of the schedule are controlled, some are variable and occur in an unpredictable manner. The variability in load metrics across the microcycle has not been explored sufficiently within the literature, despite a plethora of studies quantifying competition variability (14,16). Changes in stimuli and load are important for training adaptations within the elite setting (24).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research identified that match location had a significant influence on technical variables [17], although it had limited impact on physical variables [47]. The effect of match location on players' performance in our database is lower than those of reported in prior studies.…”
Section: Discussioncontrasting
confidence: 75%
“…Thus, teams adopting a HPBPT philosophy should consider the above variables as important indicators to adopt to allow ball retention to be maintained. This finding could also be important for recruiting players in all positions with modern central defenders and midfielders illustrating the most pronounced increases in BP related variables such as short/medium distance passes given there instrumental role in creating and maintain BP sequences in elite soccer (Bush, Archer, Hogg, & Bradley, 2015). Although the reader must be aware of the complexity of match-play and the extraneous variables not included in this analysis that could impact BP.…”
Section: Discussionmentioning
confidence: 99%